2023
DOI: 10.1021/acsami.2c21877
|View full text |Cite
|
Sign up to set email alerts
|

Gigahertz-Based Visible Light Detection Enabled via CdS-Coated TiO2 Nanotube Layers

Abstract: Detection of visible light is a key component in material characterization techniques and often a key component of quality or purity control analyses for health and safety applications. Here in this work, to enable visible light detection at gigahertz frequencies, a planar microwave resonator is integrated with high aspect ratio TiO2 nanotube (TNT) layer-sensitized CdS coating using the atomic layer deposition (ALD) technique. This unique method of visible light detection with microwave-based sensing improves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…dielectric changes due to soil moisture variation or ice accumulation 21 , 22 , or vital signs using wearable antennas 23 . Moreover, RF sensor readout has been widely used based on additional functional sensors including 2D materials 24 , conductive polymers 25 , 26 , inorganic sensitive materials 27 , lumped sensors 28 , and even bacterial cultures 29 . For gas sensing, it was shown that reading the response of resistive sensors at kHz frequencies can improve their linearity and sensitivity 30 .…”
Section: Introductionmentioning
confidence: 99%
“…dielectric changes due to soil moisture variation or ice accumulation 21 , 22 , or vital signs using wearable antennas 23 . Moreover, RF sensor readout has been widely used based on additional functional sensors including 2D materials 24 , conductive polymers 25 , 26 , inorganic sensitive materials 27 , lumped sensors 28 , and even bacterial cultures 29 . For gas sensing, it was shown that reading the response of resistive sensors at kHz frequencies can improve their linearity and sensitivity 30 .…”
Section: Introductionmentioning
confidence: 99%
“…This change can be in the refractive index, polarization, or other properties of light passing through the material. Some of the materials that performed as dielectric materials that showed electro-optic properties are TiO 2 and SiO 2 [6,7]. Heterojunction devices made of TiO 2 /SiO 2 electro-optic multilayers are controlled by applying a 100 V bias to the ends of altered the resonant modes [8].…”
Section: Introductionmentioning
confidence: 99%
“…These devices use light to control the resonance properties of a microwave cavity. They have wide range of applications including communication, sensing and signal processing [1][2][3][4][5][6][7][8][9][10][11][12]. The currently constructed resonator benefits from selenium dioxide as a sandwiched p-type layer between n-Si and p-SiO 2 .…”
Section: Introductionmentioning
confidence: 99%